A health survey of granite workers in Finland: radiographic findings, respiratory function, hearing, electric sensory thresholds of the fingers and subjective symptoms. - Ahlman, K.; Backman, A. L.; Partanen, Timo (Scandinavian Journal of Work, Environment & Health, 1975)
' ' RESULTS ': 'from a health survey of 777 granite workers, exposed to quartz dust, noise and/or machine vibration, and 122 unexposed "controls" are reported. The survey included chest X-rays, pulmonary function tests, a hearing examination, the determination of the electric sensory thresholds of the fingers, and questionnaires on the subjective symptoms of the respiratory system and upper limbs. The exposed workers' radiographic findings (except for a 2.6 % rate of silicosis), respiratory functions, and sensory thresholds did not differ significantly from those of the controls. Granite drillers had a high prevalence of hearing defects. Respiratory symptoms were common among drillers and sandblasters, and subjective symptoms of the upper limbs due to vibration occurred among the granite dressing workers who used pneumatic hammers. Both primary and secondary measures of prevention are strongly recommended for the granite industry, primarlily for quartz dust exposure and its health effects.
Keywords: dust; electric sensory threshold; finger; Finland; granite work; granite worker; health screening; health survey; hearing; noise; radiographic finding; respiratory function; subjective symptoms; vibration